the influence of social studies learning media based on Information communication and technology on the character of students' nationalism - Fadhila, Trisa Nur (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2022)
The swift current of globalization triggers increasingly complex problems, including the low character of students' nationalism. This study aims to determine the effect of using ICT-based social media learning media (Information, Communication, and Technology) on the nationalism character of students at SMP Negeri 1 Bangsal. The media in question is powerpoint, a short film that is shown through an LCD projector, assisted by the Quizizz and Edmodo applications. The research method used is quantitative research with experimental methods in the form of Pre-Experimental Design. The research design used was one group pretest-posttest. Samples were taken using non-probability sampling technique. Researchers took a sample of 32 students. The population of the study is all students of class VIII SMP Negeri 1 Bangsal for the 2021/2022 academic year, which is 256 students. The measuring instrument used is a questionnaire with a Likert scale in the form of multiple choice. The data collection technique was carried out with a closed statement through a google form. This study uses descriptive and inferential statistical analysis. Data processing, in the form of normality test, paired sample t test, and correlation test between variables assisted by SPSS version 21 program. The results showed that the calculation of the Paired sample t test obtained a sig value. of 0.000. sig value. <0.05 so H_0 is rejected and H_1 is accepted. This means that there is a difference between before and after the use of ICT-based social studies learning media. Pearson product moment correlation test results with the results 0.000 < 0.05. Pearson's value of variable X and variable Y is positive 0.602. According to the categorization interval the strength of the correlation between the two variables is included in the strong correlation.